Capacitive properties of promising energy storage material based on thiophene containing perylenediimide polymer. Issue 16 (5th November 2020) - Varol, Tuğba Ören; Topal, Sebahat; Haklı, Özgül; Sezer, Esma; Anık, Ülkü; Öztürk, Turan
Abstract: In this study, electropolymerization of pre‐synthesized N, N ′‐di‐[3‐[2‐(3‐thienyl)ethyl] phenyl] perylene‐3, 4, 9, 10‐bis(dicarboximide) (ThPDITh) was performed on Au button electrode and the properties of the resultant polymer P(ThPDITh) were investigated by electrochemical techniques. Effect of the polymerization charge on the redox behaviors of the polymer film was investigated by cyclic voltammetry (CV) and the polymer film was further characterized by electrochemical impedance spectroscopy (EIS) measurements. Corresponding electrical equivalent circuit was applied to the experimental data to explain the electrochemical phenomenon on the interface of the Au/P(ThPDITh). In order to obtain information on the energy storage properties of P(ThPDITh) as a pseudo‐capacitive electrode material, important cell characteristics, such as redox process in anodic and cathodic potential ranges, stability of galvanostatic charge–discharge (GCD) curves, coulombic efficiency, capacitance, energy and power density values were determined. Capacitance values, obtained through different measurements (CV, EIS and GCD) are all in good agreement with each other. All the results suggested that P(ThPDITh) is capable of undergoing multiple reversible redox processes, and a good candidate for improving the capacitance and energy density of electrode material while still offering high power capability. Abstract :